CFD SIMULATION AND EXPERIMENTAL STUDY ON HYDRODYNAMIC BEHAVIOUR OF TRANSESTERIFICATION REACTION IN MICROCHANNEL REACTOR - MOHD LAZIZ, AFIQ (2021)
Biodiesel as a renewable resource is important to overcome the future energy security due to the depletion of fossil fuel. Reaction of transesterification with vegetable oil and methanol is possible at room temperature, however the reaction is very slow due to the limitation on the mass transfer of the multiphase system. Microchannel reactor has the advantage of creating huge interfacial area and because of its small scale, the diffusion length is short and helps in improving mass transfer. The main objective of this current work is to study the relationship of hydrodynamic in terms of interfacial area and flow behaviour with reaction performance. The reaction performance was evaluated based on the multiphase reaction of oil and methanol in the transesterification process to produce biodiesel.